Attention deficits in Alzheimer's disease and vascular dementia. Issue 2 (9th February 2010) - McGuinness, Bernadette; Barrett, Suzanne L; Craig, David; Lawson, John; Passmore, A Peter
Abstract : Objective: To compare the performance of patients with mild–moderate Alzheimer's disease (AD) and vascular dementia (VaD) on tests of information processing and attention. Method: Patients with AD (n=75) and VaD (n=46) were recruited from a memory clinic along with dementia-free participants (n=28). They underwent specific tests of attention from the Cognitive Drug Research battery, and pen and paper tests including Colour Trails A and B and Stroop. All patients had a CT brain scan that was independently scored for white-matter change/ischaemia. Results: Attention was impaired in both AD and VaD patients. VaD patients had more impaired choice reaction times and were less accurate on a vigilance test measuring sustained attention. Deficits in selective and divided attention occurred in both patient groups and showed the strongest correlations with Mini Mental State Examination scores. Conclusion: This study demonstrates problems with the attentional network in mild–moderate AD and VaD. The authors propose that attention should be tested routinely in a memory clinic setting.